The effect of the covid-19 pandemic on sales in kemanggisan slipi market, West Jakarta - Atikah Luthfiyyah; Atiyah Fitri (Jurnal Ekonomi dan Perbankan Syariah, 2021)
This study aims to: examine the effect of the COVID-19 pandemic on sales. This research is a quantitative study using a simple linear regression method which in all tests uses the SPSS v.25. Data was obtained by distributing questionnaires directly and interviews with businesspeople in the Slipi Kemanggisan Market and a total sample of 72 respondents. Measurement of the COVID-19 pandemic is seen with the indicators of Large-Scale Social Restrictions (PSBB) and Social Distancing. The result proved that the COVID-19 pandemic affects sales at the Slipi Kemanggisan Market. This is obtained from the results of the t-value which is greater than the t-test.